Nuanced qualitative trait approaches reveal environmental filtering and phylogenetic constraints on lichen communities. Issue 4 (27th April 2022) - Koch, Natália M.; Stanton, Daniel; Müller, Sandra C.; Duarte, Leandro; Spielmann, Adriano A.; Lücking, Robert
Abstract: We propose that a qualitative trait approach based on more detailed nuanced traits may reveal previously overlooked patterns, especially when combined with phylogenetic perspectives. By sampling epiphytic lichens and using a functional approach based on nuanced qualitative traits, such as a much greater resolution over photobiont identity, type of cortex, and chemical compounds, we evaluated the effects of environmental filtering and phylogenetic constraints on community assembly along a natural succession of Atlantic rainforest. We found changes in taxonomic, functional, and phylogenetic composition, structure, and diversity. Functional traits such as photobiont genera, type of cortex, reproductive structures, propagule size, and protection strategies showed strong responses to succession. Mature forests with a closed canopy impose strong environment filtering that is reflected in lichen species turnover, limiting diversity, but also holding different functional and phylogenetic composition. The use of a nuanced qualitative trait approach may overcome some of the limitations of using this type of traits and shows the importance of often‐overlooked key lichen functional traits, including the presence of carbon‐concentrating mechanisms in photobionts and cortex properties. Furthermore, this is the first study showing how patterns of phylogenetic assembly along forest succession structure lichen communities.